Metabolomics identifies chenodeoxycholic acid as a protective factor in diabetic foot ulcers - Li, Ying; Guo, Ran; Lv, Lu; Jiang, Tao; Zhang, Chenning; Chang, Jiangying; Hu, KeYan; Peng, Huifang; Chen, Lulu; Chen, Ran; Chen, Hetao; Ma, Yujin (Frontiers in Endocrinology, 2026)
ObjectiveDiabetic foot ulcers (DFU) are a severe complication with high amputation and mortality rates, involving profound metabolic dysregulation. Current treatments lack interventions targeting the metabolic microenvironment. Chenodeoxycholic acid (CDCA) regulates glucose/lipid metabolism and inflammation, but its role in DFU remains unknown. This study aims to identify key metabolites in the serum of patients with diabetic foot ulcers. For the first time, it focuses on and identifies CDCA, a key bile acid, as an endogenous protective factor, and validates the biological role of CDCA in promoting wound healing, thereby providing a foundation for novel therapeutic strategies targeting the “metabolic microenvironment.”MethodsUntargeted metabolomics (UHPL-MS/MS) was performed on serum from 18 healthy controls, 18 diabetes mellitus (DM) patients, and 18 DFU patients. Multivariate statistics and logistic regression were used to identify differential metabolites and protective factors. In vitro, human skin fibroblasts under high glucose (30 mM) were treated with CDCA (5–25 nM). Proliferation, migration, and repair gene expression were assessed.ResultsClinical evaluation revealed that DF patients exhibited more pronounced systemic inflammation (elevated hs-CRP, ESR, and WBC), coagulation abnormalities (increased fibrinogen and D-dimer levels), and higher prevalence of vascular complications compared to other groups. Metabolomic analysis identified 41 significantly altered metabolites between the DM and DF groups, among which CDCA was markedly downregulated in the DF group (fold change = 0.66, VIP = 2.09, P = 0.008). Logistic regression analysis confirmed CDCA as an independent protective factor against DFU (OR = 0.429, 95% CI: 0.225–0.815, P = 0.010). In vitro studies demonstrated that CDCA dose-dependently reversed high glucose-induced impairment of HSF function, significantly enhancing cell proliferation and migration, and upregulating mRNA expression of PCNA, α-SMA, and Vimentin.ConclusionThis study identifies CDCA as a key protective metabolite in DF. Reduced serum CDCA levels are independently associated with increased risk of DF. Functional evidence confirms that CDCA mitigates high glucose-induced fibroblast dysfunction and promotes wound repair processes. Targeting the CDCA signaling pathway or supplementing CDCA may represent a novel therapeutic strategy for DF by remodeling the “metabolic microenvironment”.